DAMPAK INTERAKSI TINDAKAN SUPERVISI DAN PENGALAMAN KERJA TERHADAP KEPUASAN KERJA AUDITOR: STUDI EMPIRIS DI KAP YOGYAKARTA, SEMARANG DAN SOLO - Rosalina Kurniwati Tethool; Rustiana Rustiana (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2003)
The purpose of the study is to investigate the effect of interaction between supervisory action and workexperience in auditing on the auditors job satisfaction. There are 76 junior and senior auditors working inpublic accountant firms in Yogyakarta, Solo, and Semarang participate in this study. Data are collected by mail questionnaire and was analyzed by multiple regressions, and the result supports the hypothesis. It implies that managers in public accountant firms should consider the combination of supervisory act and experience in auditing in order to increase job satisfaction for senior and junior auditors.Keywords: supervisory action, work experience, job satisfaction, auditor